Expansion of the γδT cell population in peripheral blood: a response of immune system to the damage of gastrointestinal mucous membranes in older age groups - M. A. Stenina; T. V. Gromova; V. V. Grechenko; L. V. Gankovskaya (Медицинская иммунология, 2024)
γδT cells are unique lymphocytes that take an intermediate position between the cells of innate and adaptive immunity. Even at the stage of differentiation in the thymus, they acquire the status of effectors with cytotoxic activity and become powerful cytokine producers. The antigen-recognizing receptor of γδT cells formed by γ and δ chains and is assigned an important role in activation of these cells in tissues: it recognizes infected and tumor cells by the presence of intracellular stress molecules. γδT cells are found in the blood and mucous membranes. Today, researchers’ attention is focused on two subpopulations of γδT cells: γδ1 and γδ2. The first is abundantly represented in the mucous membranes, the second forms the bulk (90%) of circulating γδT cells. The aim of this study was to assess the level of circulating γδT cells in patients of older age groups with proven pathologies affecting mucous surfaces at various segments of the digestive tract. We have recruited older patients from the Russian Gerontological Research and Clinical Center aged 60 to 90 years. The main group (n = 28) included patients with lesions of the gastric mucosa and duodenum with erosive ulcerative foci. The age-matched comparison group (n = 33) consisted of patients without gastrointestinal manifestations and did not have indications for gastroduodenoscopy. A separate group (n = 35) included patients with varying degrees of colon dysbiosis. The number of γδT cells in the blood was determined by two-color flow cytofluorometry using monoclonal antibodies. Presence of erosive and ulcerative foci in the mucous membranes of the stomach and duodenum was associated with increased numbers of circulating γδT cells population. An impaired function of intestinal barrier is considered a detrimental consequence of colon dysbiosis. Among patients with severe dysbiosis (3rd degree), the proportion of patients with a high content of γδT cells was significantly higher than among patients with the 1st (milder) degree of dysbiosis. Hence, the circulating population of γδT cells in the patients of the older age group responds by increased numbers to the damage (severity of damage) of the mucous membrane observed at different segments of digestive tract. The nonspecific nature of this response is obvious. Nevertheless, the expansion of this population in the circulating blood may be a sign of particular pathological process thus requiring further advanced diagnosis.